Klinische Relevanz humaner Anti-Maus-Antikörper (HAMA) in der Immunszintigraphie - Hertel, A.; Baum, R. P.; Auerbach, B.; Herrmann, A.; Hör, G. (Nuklearmedizin - NuclearMedicine, 1990)
Murine monoclonal antibodies (MAb) are applied on a growing scale in radioimmunoscintigraphy (IS) for diagnostic and therapeutic purposes. This increasing use of xenogeneic substances in rapidly growing numbers of patients raises questions of accuracy and reliability of the MAb and also the problem of potential human immunoreaction (human anti-mouse IgG antibodies – HAMA). The aim of this study was to evaluate the clinical relevance of HAMA following IS regarding allergic complications and in vivo effects on IS after repeated applications of MAbs. Out of over 800 immunoscintigraphic examinations performed during the last 5 years in our department 289 studies (in 190 patients) with up to 10 applications (13 different MAbs all together) were considered. Only 1 patient with a high HAMA titer developed a mild allergic reaction (local urticaria) after the 3rd application of an anti-CEA MAb. In 171 intensively documented serum courses following IS, 50 (29%) showed elevated HAMA [1st application: 25/108 (23%); 2nd application: 20/41 (49%); 3rd application: 5/11 (45%); 4th – 10th application: no HAMA/11 (2 anti-CEA, 9 Antimyosin)]. Only with strongly increased HAMA values (five times the value before 1st application) there was an altered biodistribution of the MAbs in IS with partially inhibited (8/25 studies with repeated applications) tumor localization. Some patients still demonstrated positive tumor localization despite a HAMA reaction. The problem of HAMA in the diagnostic work-up using MAbs is not the allergic reaction but the potential effects on IS in repeated studies. HAMA should be measured prior to repeated immunoscintigraphic studies.